RADIOPROTECTION: MECHANISMS AND RADIOPROTECTIVE AGENTS INCLUDING HONEYBEE VENOM - Varanda, E. A. [UNESP]; Tavares, D. C. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 1998)
Since 1949, a great deal of research has been carried out on the radioprotective action of chemical substances. These substances have shown to reduce mortality when administered to animals prior to exposure to a lethal dose of radiation. This fact is of considerable importance since it permits reduction of radiation-induced damage and provides prophylactic treatment for the damaging effects produced by radiotherapy. The following radioprotection mechanisms were proposed: free radical scavenger, repair by hydrogen donation to target molecules, formation of mixed disulfides, delay of cellular division and induction of hypoxia in the tissues. Radioprotective agents have been divided into four major groups: the thiol compounds, other sulfur compounds, pharmacological agents (anesthetic drugs, analgesics, tranquilizers, etc.) and other radioprotective agents (WR-1065, WR-2721, vitamins C and E, glutathione, etc.). Several studies revealed the radioprotective action of Apis mellifera honeybee venom as well as that of its components mellitin and histamine. Radioprotective activity of bee venom involves mainly the stimulation of the hematopoietic system. In addition, release of histamine and reduction in oxygen tension also contribute to the radioprotective action of bee venom.
Keywords: radiation; protective agents; honeybee venom